Evaluating the Agronomic Characteristics and Nutritional Quality of Silage from Various Maize (Zea mays) Varieties - Sanjyal , Sunita; Acharya, Rabin; Acharya, Arjun Acharya; Bohara, Shishir Singh (Journal of the Institute of Agriculture and Animal Science, 2024)
High-quality fodder is one of the most essential components of Livestock feeding as it ensures that animals meet their nutritional requirements. Maize (Zea mays) silage provides an important solution to mitigate herbage shortages during lean periods, helping to counteract the rising feed prices. A study was conducted at Lamjung Campus, Lamjung, from March to July 2023 to assess the quality of silage produced from seven maize varieties: MX-77, Pioneer, Rampur Hybrid-10, Raj Kumar, CP-666, All Rounder, and CP-838. The experiment was carried out with three replications in a randomized complete block design. The chemical composition of the silage was analyzed to determine the dry matter content, crude protein, crude fiber, neutral detergent fiber (NDF), acid detergent fiber (ADF), and pH. The agronomic traits like plant height, stem diameter, 50% tasseling, leaf number, leaf area and herbage yield were also recorded. Results showed a significant difference in agronomic and chemical traits where MX-77 had the herbage yield (25.76 MTha-1), plant height (208.556cm) and crude protein (7.91) which was comparable to the Pioneer variety. The least was recorded for variety Raj Kumar (4.36). Rampur Hybrid-10 took the longest duration (84.67 days after sowing) to reach the 50% tasseling stage, while CP 666 was the earliest variety to reach 50% tasseling at 72.66 days after sowing. MX-77 and Pioneer were identified as the best varieties for quality silage production, offering higher herbage yield (HY), dry matter yield (DMY), and crude protein (CP). Acid detergent fiber (ADF) was highest in CP 838 (45.1%), indicating lower digestibility and nutritional value of the silage, while the lowest ADF was found in Raj Kumar (30.71%). HY in maize showed moderate positive correlations with leaf area (r = 0.57**, p < 0.01), stem diameter (r = 0.45*, p < 0.05), and plant height (r = 0.54*, p < 0.05), as well as with crude protein (r = 0.68***, p < 0.001) and crude fiber (r = 0.6**, p < 0.01). Furthermore, ADF and neutral detergent fiber (NDF) were positively correlated with dry matter (DM) percentage (r = 0.5*, p < 0.05; r = 0.49*, p < 0.05), with delayed maturity leading to increased ADF (r = 0.56*, p < 0.01) and reduced digestibility. This study offers valuable insights for farmers and livestock producers in selecting the most suitable maize varieties for silage production to ensure high yields and superior nutritional value for livestock.